Analysis Content Validity of Electronic Records for learning to improve the skills of the Archives Practice Course in Higher Education: Aiken Validity and Lawshe (Educational Management, 2022)
Pre-service teachers have an essential role in the education sector. They are given training and education to provide quality learning services in the future. For this reason, we seek to assess learning media as a critical and complex step to investigate the feasibility of learning media being used to teach prospective teachers. The purpose of this study was to investigate the elements of the validity of evaluation instruments and learning media for archiving courses in tertiary institutions. A practical approach through content validity is used to find existing content validity indices. So far, this research is included in the narrative review of the assessment and quantification of content validity. We distributed the questionnaire to at least five expert judgments of experts and practitioners in learning and office administration. The study's results found that learning media in the form of electronic records were stated to be very valid according to the Lawshe method, and the evaluation instruments were declared valid based on the Aiken method. In the future, we propose to use evaluation instruments and Electronic Records, which are widely tested.